Urgency of Implementing Article 1365 of the Civil Code in Addressing Tortious Conduct in Electronic Transactions in Indonesia - Ahmad Rizky Siregar; Wieke Dewi Suryandari; Hono Sejati (Riviera Publishing, 2024)
The rapid growth of electronic transactions has introduced new challenges, particularly concerning tortious conduct and the legal framework governing these interactions. In an increasingly digital era, electronic transactions have become a primary medium for commerce and business interactions, yet issues such as fraud and personal data violations have become more prevalent. Article 1365 provides a legal basis for individuals or entities suffering damages to file claims for compensation. This study examines the urgency of implementing Article 1365 of the Civil Code in addressing tortious conduct within electronic transactions in Indonesia. The objective is to analyze the applicability, limitations, and potential reforms needed to adapt Article 1365 to the digital context. A normative legal research method was employed, utilizing a statute and conceptual approach. Data were collected by analyzing legislative texts, legal literature, and case law. Data analysis involved qualitative content analysis to identify gaps and propose solutions. The findings reveal that Article 1365 provides a strong foundation for addressing tortious conduct, but its application in electronic transactions remains ambiguous, particularly regarding evidence collection and the definition of harm. This research introduces a novel perspective by emphasizing the necessity for specific regulations and institutional reforms to enhance legal certainty and address the unique challenges posed by electronic transactions. These recommendations aim to protect consumer rights, ensure fair business practices, and foster trust in Indonesia’s digital economy.